An ex-ante analysis of the impact of biofortified zinc rice on dietary zinc inadequacy: Evidence from Bangladesh, Indonesia, and the Philippines - De Moura, Fabiana F.; Moursi, Mourad; Angel, Moira Donahue; Angeles-Agdeppa, Imelda; Muslimatun, Siti; Atmarita, Atmarita; Gironella, Glen M.; Boy, Erick; Carriquiry, Alicia (Elsevier, 2024)
Background: South, East, and Southeast Asia are among the regions of the world with the highest estimated prevalence of inadequate zinc intake. Because populations in those regions eat rice as their main staple, zinc biofortification of rice can potentially improve zinc intake, especially among the most vulnerable. Objectives: We modeled the impact of the consumption of zinc-biofortified rice on zinc intake and inadequacy among women of childbearing age and young children nationally in Indonesia, the Philippines, and at a subnational level in Bangladesh. Methods: We conducted an ex-ante analysis by applying increments of zinc content in rice, from a baseline level of 16 parts per million (ppm) to 100 ppm, and based on rice consumption data to substitute levels of conventional rice with zinc-biofortified rice varying between 10% and 70%. Results: Among all datasets evaluated from these 3 countries, the prevalence of dietary zinc inadequacy at baseline was 94%–99% among women of childbearing age, 77%–100% among children 4–5 y old, and 27%–78% among children 1–3 y old. At the current breeding target of 28 ppm, zinc-biofortified rice has the potential to decrease zinc inadequacy by ≤50% among women and children in rural Bangladesh and among children in the Philippines where consumption of rice is higher compared with Indonesia. Conclusions: Our analysis shows that increasing zinc content in rice ≤45 ppm reduces the burden of zinc inadequacy substantially, after which we encourage programs to increase coverage to reach the highest number of beneficiaries.